REALIZATION OF THE PARABLE ABOUT THE PRODIGAL SON IN YE. RUDYI’S WEST UKRAINIAN DRAMA «HERE IS THE LAND OF THE ANCESTORS OF MINE» - . Rodchyn, Z. Ya (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The work of West Ukrainian dramatist Ye. Rudyi is analyzed in the article. The phenomenon of transformation of a parable into a motif against the background of the main character’s existentialistic search is in the center of the research work.